Statement by the Managing Director on the Work Program of the Executive Board Executive Board Meeting : June 10, 2021. (Policy Papers; Policy Paper, 2021)
An unprecedented policy response and rapid progress in vaccinations have helped pull the global economy from a deep recession, but the outlook is marked by high uncertainty and great divergence. Against this background, the Fund continues its efforts to achieve a durable exit from the crisis, minimize long-term scarring, and build a more sustainable, resilient, and inclusive global economy. In line with the strategic directions laid out in the Spring 2021 Global Policy Agenda and the International Monetary and Financial Committee (IMFC) Communique, this Work Program puts forward a prioritized Board agenda focused on activities of most critical importance to our members.